THE HOME INDUSTRY'S STRATEGIES OF WOODCRAFT FOR INCREASING SALES THROUGH THE PROMOTION IN SOCIAL MEDIA BY INSTAGRAM - Siti Mariam; Fika Aryani (Jurnal Ekonomi, 2023)
This study addresses using social media as a targeted marketing approach to promote and advertise products. The emphasis on this aspect becomes significant when utilizing social media as a platform that enables direct and efficient communication with the intended audience. The main objective of this research is to describe the process of planning, implementing, monitoring, and identifying obstacles and solutions implemented through the Instagram social media platform to increase sales volume in the woodcraft home industry sector. This research employed a qualitative approach with a descriptive system. This method permits researchers to understand how Instagram is integrated into woodcraft marketing strategies thoroughly. The results of this study cover two main aspects: First, planning, implementation, and monitoring are implemented as a powerful communication tool to carry out the marketing process. Second, it was found that the obstacles faced included increasing business competition in an increasingly crowded market. The solution found is to increase promotional activities through social media. This study enhances the comprehension of the efficacy of social media platforms, particularly Instagram, as a marketing instrument for augmenting sales within the woodcraft home industry domain. The practical implications of this research can provide guidance for businesses in designing and implementing more careful and effective marketing strategies through social media, as well as overcoming obstacles that may arise in the process.